DAMPAK PENGUMUMAN PENERAPAN TEKNOLOGI INFORMASI TERHADAP NILAI PERUSAHAAN - Herdratmoko, Mohamad; ACHJARI, DIDI (Fakultas Bisnis UKDW, 2008)
Nowadays, orgonizations tend to invest highty in infprmation technologt However the notion of podrctivity puadox indicates that the investments may not attain intended results. past studies show that the relationship between IT investment and productivity/company performmce shows mixed results. This sttt aims to investigate-market reaction towwds IT implementatibn (mnotn cement in the context of Indonesia.The implementation is expected to provide a signal to tie market since it may have information content of pontential future economic benefits. The current research employs datafrom Inionesia stock Exchange fformerly btown as Bursa Efek Jakarta - BEq. The ziest was used to analyze the data. unfortunately, data analysis results indicate that the average abnormal rehnn before (t-1) and afier (t+t) the doy ofonnouncem9yt has no significant dffirence. The results suggest lhat iT implementition announcement have no- information-iontent for Indonesia's capital market/investor Lesson learnedfrom the current ,iray, is that, in the cgwext of Indonesia, IT implementation is not perceived tolead to produc"tivity improvement.Keywords : e-business, IT implementation, event study, productivity paradox, Jakarta Stock Exchange (Bursa Efek Jakarh), market reaction, IT investment.",